THE EFFECT OF PLYOMETRIC TRAINING AND LOWER LIMB FLEXIBILITY ON DOLLYO CHAGI KICKING ABILITY IN TAEKWONDO GLADIATOR ATHLETES IN SEMARANG - Dondi, Dondi Eko Meilani (Journal of Physical Education and Sports, 2025)
The background of this study is the suboptimal dollyo chagi kicking ability among the taekwondo athletes of Gladiator Semarang. The research problem focuses on the lack of effectiveness in dollyo chagi kicks by taekwondo athletes of Gladiator Semarang during competitions. This research aims to analyze the impact of plyometric training and lower limb flexibility on the speed of dollyo chagi kicks by taekwondo athletes of Gladiator Semarang. This experimental study used a 2x2 factorial design. The population consisted of 40 taekwondo athletes of Gladiator Semarang, with a sample of 32 athletes selected through purposive sampling based on specific criteria (flexibility). The instruments included a lower limb flexibility test (side split) and a dollyo chagi speed test. Data analysis employed ANOVA (two-way). The results indicated: 1) Significant differences in the effects of single-leg hurdle hop training 0,002 (better) compared to single-leg bounding. 2) Significant differences in lower limb flexibility, with higher flexibility showing 0,000 < 0.05. 3) Significant interaction between plyometric training and lower limb flexibility on kick speed. In conclusion, using single-leg hurdle hop and single-leg bounding, plyometric training can significantly improve dollyo chagi performance, especially when adjusted to the athlete's lower limb flexibility level. These methods are recommended for training programs, with intensity and variations adjusted to the athlete's needs and characteristics.